ANALISIS PENGARUH INFLASI, SUKU BUNGA, DAN KURS TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) 2019-2024 - Andreas Purba; Jason Siswanto; Sean William Gunawan; Aulia Nurul Huda (Universitas Muhammadiyah Bengkulu, 2025)
This study aims to analyze the influence of macroeconomic variables—inflation, the benchmark interest rate (BI 7-Day Reverse Repo Rate), and the rupiah exchange rate against the US dollar—on the movement of the Composite Stock Price Index (IHSG) in Indonesia during the period from January 2019 to December 2024. The method used is a quantitative approach with time series analysis using the Vector Error Correction Model (VECM), equipped with a stationarity test, optimal lag test, Johansen cointegration test, Granger causality test, and Impulse Response Function (IRF) and Variance Decomposition analysis. The results of the study indicate that inflation and the benchmark interest rate have a positive and significant effect on the IHSG in the short and long term, although contrary to conventional theory. The rupiah exchange rate has a negative effect on the IHSG in the short term, but turns positive in the long term. In addition, the IHSG shows a rapid adjustment mechanism towards long-term equilibrium (error correction coefficient of -53.14%). This finding emphasizes the importance of exchange rate dynamics as a dominant variable, and provides strategic implications for investors and policy makers in managing Indonesian stock market sentiment. Keywords: Inflation, BI 7-Day Reverse Repo Rate, Rupiah/USD Exchange Rate